Community's perceptions towards learning music in schools / Wan Fazliani Wan Yusoff - Wan Yusoff, Wan Fazliani (Faculty of Music, 2016)
Music is broadly-known in Malaysia community. As the community becomes more interested in music, music has been taught in schools. Nowadays, learning music seems to be not important in schools. This can be seen through the music education learning period in schools that have been shortened from sixty minutes per period to thirty minutes per period (Feride, 2014). It can be that learning music is not that important to be taught in schools or parents of the children also agree that music period should be shorter than the other subject period at schools. This matter has related to how community thinks about music education. Previous research has researched on how public perceptions of music (Austin, 2011). Issues that related to music education might affect the perceptions towards learning music in schools. The problems that might affect the perception toward learning music is music that been taught by the non - music specialist (Holden and button (Ed) 2006). Meanwhile, Wright (Ed) 2001) stated that the gender is an issue in learning music. The achievement in music education between boys and girls were different and Wright (Ed) 2001) has found that the boys were faster learner than the girls.